5(t-2)+6(t-3)=5

Simple and best practice solution for 5(t-2)+6(t-3)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(t-2)+6(t-3)=5 equation:


Simplifying
5(t + -2) + 6(t + -3) = 5

Reorder the terms:
5(-2 + t) + 6(t + -3) = 5
(-2 * 5 + t * 5) + 6(t + -3) = 5
(-10 + 5t) + 6(t + -3) = 5

Reorder the terms:
-10 + 5t + 6(-3 + t) = 5
-10 + 5t + (-3 * 6 + t * 6) = 5
-10 + 5t + (-18 + 6t) = 5

Reorder the terms:
-10 + -18 + 5t + 6t = 5

Combine like terms: -10 + -18 = -28
-28 + 5t + 6t = 5

Combine like terms: 5t + 6t = 11t
-28 + 11t = 5

Solving
-28 + 11t = 5

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '28' to each side of the equation.
-28 + 28 + 11t = 5 + 28

Combine like terms: -28 + 28 = 0
0 + 11t = 5 + 28
11t = 5 + 28

Combine like terms: 5 + 28 = 33
11t = 33

Divide each side by '11'.
t = 3

Simplifying
t = 3

See similar equations:

| -8+y=-3 | | 3x+2x=4(x-3) | | 22000+0.04x=55000 | | 25b^2+40bg+16g^2= | | 20-3b=8 | | 22y^2-10y+5= | | -2=2j-8 | | 11x-2(2x+3)=7 | | (4x-2)-(-2x-4)=12 | | 2x+40=10-40 | | 4abs(x+3)=20 | | 10y+16x=900 | | 3(5x-(7-7y+7x)+7y)= | | 14+3n=4n-3(n-4) | | 120n-120=600 | | R-2y=14 | | 5(6x+8)=10(7x+6) | | 2x+3=3(1-X) | | -1k=9(1k+-10) | | 35r^2-40r+21r-24=0 | | 3=-5+2w | | 8n-4=60 | | 48-5x=-8+5 | | 18n+45=441.00 | | 20v=-35 | | -8x-(3x+6)=4-2 | | 4(x+14)=-20 | | x+0.07=24160 | | 28+4x=9x | | c^2-6c-c+6=0 | | 28+4=9x | | -10y+18=-15y-15y |

Equations solver categories